Frequency spectrum analysis of mixed-line rate in flexible optical networks - Suthaharan, S.; Rukshani, P.; Vanuja, C. (University of Jaffna, 2019)
Optical networking is a promising solution of Internet growth since it uses wavelength division multiplexing technique [1]. The ever increasing demand for bandwidth is posing new challenges for transport network providers. A feasible solution to meet such challenge is to use optical networks with the aid of WDM technology. WDM is a multiplexing technique of data transmission in which it divides the huge transmission bandwidth available ona fiber into several non-overlapping wavelength channels and enables data transmission over these channels simultaneously [2]. WDM is mostly used for optical fiber communications to transmit data in several channels with slightly different wavelengths. WDM uses a multiplexer at the transmitter and a demultiplexer at the receiver to join the several signals together and to split them apart respectively. The channels in WDM are typically using 50 GHz or 100 GHz rigid grid spectrum spacing as specified by the International Telecommunication Union (ITU) [3]. For instance, 50 GHz fixed grid space is capable to transmit 100 Gbps based transmission rate and commercialized [4] . In our research study, we have focused on shared protection method in WDM optical networks. A single fiber consists of 4.4 THz total spectrum width which can be divided into 88 channels each of 50 GHz fixed grid [5] . Flexible optical networks (or Elastic optical networks (EON)) have recently been introduced to use the frequency spectrum more efficiently [4]. 12.5 GHz fine granular frequency slots or flexible grids are used for setting up lightpaths instead of using 50 GHz or 100 GHz fixed grid spacing in flexible optical networks [6] . Optical fiber has a risk of failure in terms of fiber-cut which causes loss of huge amount of data and therefore, the communication services can be interrupted. In survivability, the path through which transmission is actively realized is called working path or primary path whereas the path reserved for recovery is called backup path or secondary path. Protection is one of the approaches in survivability of optical networks in which pre-assigned backup paths are setup or reserved at the time of admitting a connection which are link-disjoint with their corresponding primary paths. Shared protection is one of the traditional protection methods in which backup resources can be shared by the backup paths or secondary paths. Spectrum efficiency is the optimized use of spectrum so that the maximum amount of data can be transmitted with the fewest transmission errors. Spectrum efficiency can be computed by dividing the total traffic data rate by the total spectrum used in a particular network. The total traffic data rate can be computed by multiplying the data rate by the number of connections. The total spectrum will be the multiplication of the frequency used for a single wavelength and the total number of wavelengths used in a network [7] . To the best of our knowledge, this is the first paper that is investigating variation of the spectrum efficiency of traditional shared protection and flexible optical networks using mixed-line rate(MLR) in various scenarios. Our findings are as follows. The spectrum efficiency of MLR is significantly varied, when applying traditional shared protection in EON. Unlike spectrum efficiency of MLR in dedicated protection, spectrum efficiency of MLR in shared protection method is considerably higher. Finally, spectrum efficiency in MLR using EON is significantly varied when compared to spectrum efficiency in MLR using WDM.